2010
DOI: 10.1007/s00216-010-3936-9
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of bisphenol A from thermal printer paper to the skin

Abstract: Of 13 thermal printing papers analyzed, 11 contained 8-17 g/kg bisphenol A (BPA). When taking hold of a receipt consisting of thermal printing paper for 5 s, roughly 1 microg BPA (0.2-6 microg) was transferred to the forefinger and the middle finger if the skin was rather dry and about ten times more if these fingers were wet or very greasy. This amount transferred to dry skin was neither significantly increased when taking hold of the paper at up to 10 sites, nor reduced when BPA-free paper was contacted afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
296
2
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 373 publications
(314 citation statements)
references
References 4 publications
7
296
2
5
Order By: Relevance
“…Tens to hundreds of micrograms of BPA can be released from heat‐printed receipts 87. The estimated overall exposure to BPA through thermal paper contact was 7.1–42.6 µg day –1 for the general population and 71 µg per day for a cashier after a ten hour shift 88. The urine concentration of BPA detected in cashiers (2.4 µg g –1 ) was also found to be higher than that of the general population (1.2 µg g –1 ) 89.…”
Section: Sources and Routes Of Bpa Exposure In Everyday Settingsmentioning
confidence: 88%
“…Tens to hundreds of micrograms of BPA can be released from heat‐printed receipts 87. The estimated overall exposure to BPA through thermal paper contact was 7.1–42.6 µg day –1 for the general population and 71 µg per day for a cashier after a ten hour shift 88. The urine concentration of BPA detected in cashiers (2.4 µg g –1 ) was also found to be higher than that of the general population (1.2 µg g –1 ) 89.…”
Section: Sources and Routes Of Bpa Exposure In Everyday Settingsmentioning
confidence: 88%
“…During the mobile phase, methanol and milli-Q water (purified by an ultrapure water system; Barnstead International, Dubuque, IA), at a gradient starting with 15% methanol at 0 min, was held for 2 min; increased to 90% methanol at 2 to 9 min; then increased to 99% methanol at 9 to 12 min, held for 3 min; and finally reversed to 15% methanol, held for 5 min before the next injection. The negative ion multiple reaction monitoring (MRM) mode was used, and the MRM transitions monitored were 249 > 108 for BPS (98%; Sigma-Aldrich, St. Louis, MO) and 239 > 224 for 13 C 12 −BPA. Nitrogen was used both as a curtain and a collision gas.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Exposure to BPA occurs through many sources, including reusable water bottles, baby bottles, metallic food cans, thermal paper, carbonless copy paper, and consumer electronics including computers, cell phones, and video game consoles. Indeed, a recent study found that BPA was transferred to the skin after handling receipts printed on thermal paper, although the authors were not able to assess the levels of BPA that actually penetrated into the systemic circulation (11). More research is needed before a proper evaluation of the ability of BPA to cause systemic effects after dermal exposure can be made.…”
mentioning
confidence: 99%